1987
DOI: 10.1159/000124761
|View full text |Cite
|
Sign up to set email alerts
|

Histaminergic Neuromodulation of the Release of Vasopressin

Abstract: In an attempt to clarify the nature of histaminergic neuromodulation of the vasopressinergic system, several studies under different experimental paradigms were carried out. L-Histidine loads (8 mmol/kg, i.p.) induced a marked increase in histamine (HA) in the anterior (AHR) and posterior (PHR) hypothalamic regions, the median eminence (ME) and adenohypophysis (Ah) with no apparent effect on the concentration of HA in the neurohypophysis (Nh), as measured by high-performance liquid chromatography. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…In this study, not only a small dose of histamine, but also C48/80, evoked a significant increase in plasma ADH. It is well known that histamine given into the cerebral ventricle greatly elevates ADH secretion (2,7,15,57,63). When we administered 37.5 g/kg C48/80 into the V III , the increase in ADH from the basal level (2.6 times) was roughly equal to that in PRA (2.3 times).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this study, not only a small dose of histamine, but also C48/80, evoked a significant increase in plasma ADH. It is well known that histamine given into the cerebral ventricle greatly elevates ADH secretion (2,7,15,57,63). When we administered 37.5 g/kg C48/80 into the V III , the increase in ADH from the basal level (2.6 times) was roughly equal to that in PRA (2.3 times).…”
Section: Discussionmentioning
confidence: 79%
“…Antidiuretic hormone (ADH), along with the renin-angiotensin system, is of great importance in regulating the defenses against both stress and cardiovascular dysfunction (57). The stress-induced increases in both renin secretion (5,14,29,30,33,44,55) and ADH (2,7,15,57) depend upon increases in the production of histamine and its receptors. Thus, these data seem to suggest that in the regulation of both renin and ADH secretion during stress reactions, histamine may act as a neurotransmitter within the hypothalamus (14,25,33,54,59).…”
mentioning
confidence: 99%
“…Centrally administered SS produces a dose-related decrease in histamine levels in the rat hippocampus [7]. Ample evidence exists for histaminergic projections to the hippocampus [33,53], a brain area rich in SS content and receptors [21,40].…”
Section: Introductionmentioning
confidence: 99%
“…Cacabelos et al 1984, 1985a, b ; Cacabelos et al 1985bCacabelos et al , 1987 or neuroregulator (Prell and Green 1986). HA cell bodies are located in the posterior region of the hypothalamus (Panula et al 1984 ; Steinbusch and Mulder 1984 ;Watanabe et al 1984 ;Senba et al 1985) sending axons in apparently organized ascending and descending pathways to the cortex (Takeda et al 1984) and spinal cord (Wahlestedt et al 1985).…”
mentioning
confidence: 99%
“…Our previous neurochemical studies suggested that there are three main intrahypothalamic HA pathways from the posterior hypothalamus to the anterior hypothalamus, median eminence and neurohypophysis (Cacabelos 1984(Cacabelos , 1985bCacabelos et al 1985b), where abundant HA fibers are detected by immunohistochemical methods using antibodies against HA (Steinbusch and Mulder 1984) and histidine decarboxylase ; Senba et al 1985 ; Inagaki et al, unpublished data). These intrahypothalamic HA pathways are supposed to regulate neuroendocrine functions (Cacabelos 1984(Cacabelos , 1985a and particularly corticotropinergic (Cacabelos et al 1983Cacabelos 1984Cacabelos , 1985b) and vasopressinergic (Cacabelos 1984(Cacabelos , 1985bCacabelos et al 1987) systems. However, HA can also influence other neuroendocrine axes, as described in several reviews (Weiner and Ganong 1978;Roberts and Calcutt 1983;Cacabelos 1984Cacabelos ,1985a, b ; Donoso and Alvarez 1984; Tuomisto and Mannisto 1985).…”
mentioning
confidence: 99%